Possible and probable errors in child language - Brogden Payne, Sarah (Yearbook of the Poznan Linguistic Meeting, 2025)
This paper investigates the implications of Blind Alley Developments (BADs, Dressler et al. 2020) – ephemeral, systematic errors in early child productions – for a theory of language acquisition. I argue that a sufficient theory of acquisition should not simply allow for BADs, but rather should precisely account for the timeline and content of these errors in terms of the learning mechanisms that the child employs; in other words, it should be a learning theory. I present such an account, which draws on the complementary approaches of the Tolerance Principle (Payne & Yang 2023) and Natural Morphology (Dressler et al. 2020). This account provides both a formalization of the timeline of BADs – in terms of a calibration of productivity over the learner’s internal vocabulary – and predictions regarding the expected types of BAD constructions. I provide applications of this account to both weak BADs – which involve the use of an incorrect form that nevertheless marks the correct target function – and strong BADs – which involve the use of a form never used for the target function in the learner’s input.